Resonance-stabilized radical clustering bridges the gap between gaseous precursors and soot in the inception stage - Hong Wang; Jiwen Guan; Guangxian Xu; Xavier Mercier; Jinyang Zhang; Haotian Guo; Tongzhu Yu; Huaqiao Gui; Teng Huang; Donald G. Truhlar; Zhandong Wang (Proceedings of the National Academy of Sciences, 2025)
Carbonaceous particles are widespread in combustion, atmospheric, extraterrestrial, and nanomaterials environments. Resonance-stabilized radicals (RSRs) are commonly identified in fuel combustion and pyrolysis processes and play an essential role in carbonaceous particle formation. Despite their importance, comprehensive experimental and mechanistic understanding of particle inception through RSR reactions is lacking. This work investigated particle size distribution, chemical composition, and thermal behavior of soot particles generated by the flow reactor pyrolysis reactions of typical RSRs, in particular, 1-indenyl, 1-methylnaphthyl, and 2-methylnaphthyl radicals, and by the pyrolysis of hydrocarbons with a variety of structures. Particle size distributions show soot particles with mobility diameters in an incipient-particle range of 1.3 to 1.6 nm. Laser desorption/ionization mass spectrometry results suggest that soot products consist of much larger covalently bound clusters (CBCs) than those observed in the gas phase. Under our experimental conditions, the CBCs exhibit a phase transition for particles with calculated molecular diameters of around 1.5 nm. Evaporation experiments and thermogravimetric analysis of the soot products reveal distinct thermal characteristics for small and large CBCs. These results implicate CBCs as bridges between gas-phase species and soot particles. The present work provides a soot-inception mechanism called RSR clustering (RSRC) that is characterized by the reactive clustering of RSRs. The RSRC mechanism contrasts with conventional soot formation models that attribute soot inception primarily to the aggregation of large-size polycyclic aromatic hydrocarbons.